Abnormal functional connectivity of thalamic sub-regions contributes to fatigue in multiple sclerosis. (August 2018) - Hidalgo de la Cruz, Milagros; d'Ambrosio, Alessandro; Valsasina, Paola; Pagani, Elisabetta; Colombo, Bruno; Rodegher, Mariaemma; Falini, Andrea; Comi, Giancarlo; Filippi, Massimo; Rocca, Maria Assunta
Objective: To investigate sub-regional thalamic resting-state (RS) functional connectivity (FC) abnormalities in multiple sclerosis (MS) and their correlation with fatigue and its subcomponents (physical, cognitive, and psychosocial). Methods: From 122 MS patients and 94 healthy controls, 5 thalamic sub-regions (frontal, motor, postcentral, occipital, temporal) were parcellated based on their cortico-thalamic structural connectivity and used for a seed-based RS FC analysis. Abnormalities of thalamic RS FC in MS patients and their correlation with Modified Fatigue Impact Scale (MFIS) were assessed. Results: Compared to controls and non-fatigued MS ( n  = 86), fatigued MS patients ( n  = 36) showed thalamic RS FC abnormalities with middle frontal gyrus, sensorimotor network, precuneus, insula, and cerebellum, which correlated with global MFIS. Higher thalamic RS FC with precuneus and lower RS FC with posterior cerebellum correlated with cognitive MFIS. Higher thalamic RS FC with sensorimotor network in frontal-, motor-, and temporal thalamic sub-regions correlated with physical and psychosocial MFIS. Reduced thalamic RS FC with right insula in motor-, postcentral-, and occipital thalamic sub-regions correlated with psychosocial fatigue. Conclusion: Regional thalamic RS FC abnormalities with different cortical regions, including the frontal lobe, sensorimotor network, precuneus, insular cortices, and cerebellum contribute to fatigue in MS. Abnormal RS FC of selected thalamo-cortical connections explains different components of fatigue.